Keterbukaan Diri Melalui Cyber Counseling (Studi Kasus Layanan Konseling Individual Pada Siswa MTS Zia Salsabila) - Dinda Hidjayanti; Ivo Liza Miranda; Nur Azizah; Nursholihat Ujung; Rizka Aulia Yanda; Sartika Dara Alida Harahap (Student Scientific Creativity Journal, 2023)
Self-disclosure through cyber counseling or online counseling has become increasingly popular in recent years. This is because more and more people feel comfortable seeking counseling or psychotherapy help online rather than in person. Advances in communication technology and the internet have made online counseling more accessible and acceptable to many people. Online counseling also provides clients with greater anonymity and privacy, allowing them to be more open about the problems they face. In addition, online counseling also provides convenience in terms of time and place. Clients do not need to come to the counseling place in person, so they can save time and transportation costs. Online counseling also allows clients to conduct counseling sessions from a comfortable and safe place for them. However, keep in mind that online counseling also has some drawbacks. One of them is the lack of social interaction which can affect the counselor’s ability to observe the client’s body language and facial expressions. In addition, online counseling also requires higher technology and data security skills to maintain client privacy and confidentiality.